2019
DOI: 10.1007/s12410-019-9491-7
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Imaging of Atherothrombotic Diseases

Abstract: Purpose of Review A variety of approaches and molecular targets have emerged in recent years for radionuclide-based imaging of atherosclerosis and vulnerable plaque using single photon emission computed tomography (SPECT) and positron emission tomography (PET), with numerous methods focused on characterizing the mechanisms underlying plaque progression and rupture. This review highlights the ongoing developments in both the pre-clinical and clinical environment for radionuclide imaging of atherosclerosis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…PET imaging of arterial inflammation and atherosclerosis has also garnered attention in the cardiology community in the past decade, with a large majority of published studies focusing on the application of fluorine-18 ( 18 F)-fluorodeoxyglucose (FDG) and 18 F-sodium fluoride (NaF) for molecular imaging of inflammation and atherosclerotic disease progression in the carotid arteries, coronary arteries, and aorta (31). 18 F-FDG in particular continues to be one of the most widely used PETbased approaches for assessing arterial inflammation due to it being a glucose analog that possesses an affinity for metabolically active macrophages that are present in inflamed atherosclerotic plaques (32)(33)(34).…”
Section: Molecular Imaging Of Peripheral Artery Inflammation and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…PET imaging of arterial inflammation and atherosclerosis has also garnered attention in the cardiology community in the past decade, with a large majority of published studies focusing on the application of fluorine-18 ( 18 F)-fluorodeoxyglucose (FDG) and 18 F-sodium fluoride (NaF) for molecular imaging of inflammation and atherosclerotic disease progression in the carotid arteries, coronary arteries, and aorta (31). 18 F-FDG in particular continues to be one of the most widely used PETbased approaches for assessing arterial inflammation due to it being a glucose analog that possesses an affinity for metabolically active macrophages that are present in inflamed atherosclerotic plaques (32)(33)(34).…”
Section: Molecular Imaging Of Peripheral Artery Inflammation and Atherosclerosismentioning
confidence: 99%
“…Historically, 18 F-NaF was originally approved in the 1960s and used for targeted imaging of bone remodeling due to its high affinity for hydroxyapatite, the mineral form of calcium apatite (39). However, in the last 10-15 years, a large body of cardiovascular literature has emerged that has explored the utility of 18 F-NaF as a tool for quantifying the active process of vascular microcalcification (31). As with 18 F-FDG, 18 F-NaF has only recently been applied and investigated in the setting of lower extremity PAD.…”
Section: Molecular Imaging Of Peripheral Artery Inflammation and Atherosclerosismentioning
confidence: 99%
“…Positron emission tomography (PET) imaging with fluorine-18 ( 18 F)-sodium fluoride (NaF) has emerged in recent decades as an approach for identifying the active process of vascular microcalcification in coronary arteries [23][24][25][26], and not until recent years have studies begun to translate 18 F-NaF PET/CT imaging to the lower extremities. These lower extremity studies have shown that femoral artery uptake of 18 F-NaF is associated with increased levels of plasma total cholesterol and hemoglobin A1c [27] and may predict femoral artery calcium progression [28].…”
Section: Introductionmentioning
confidence: 99%
“…PET/CT also demonstrated increased focal uptake of 18 F-NaF in 2 distal vascular sites ( B and C , arrows) that did not coincide with prominent macrocalcification on CT images, thereby indicating potential early stages of microcalcification in additional atherosclerotic plaques. 18 F-NaF PET/CT imaging has emerged as a tool that offers dual assessment of macrocalcifications (via CT) and the process of active microcalcification associated with atherosclerosis (via 18 F-NaF PET), 1 with 18 F-NaF uptake being shown to localize to arterial segments that are undergoing active microcalcification. 2 , 3 Although 18 F-NaF PET/CT imaging investigations have traditionally evaluated coronary artery plaque remodeling, 1 recent work has also begun to assess the utility of PET/CT for evaluating abdominal aortic aneurysms, 4 – 7 carotid arteries, 8 , 9 and femoral arteries.…”
mentioning
confidence: 99%
“…18 F-NaF PET/CT imaging has emerged as a tool that offers dual assessment of macrocalcifications (via CT) and the process of active microcalcification associated with atherosclerosis (via 18 F-NaF PET), 1 with 18 F-NaF uptake being shown to localize to arterial segments that are undergoing active microcalcification. 2 , 3 Although 18 F-NaF PET/CT imaging investigations have traditionally evaluated coronary artery plaque remodeling, 1 recent work has also begun to assess the utility of PET/CT for evaluating abdominal aortic aneurysms, 4 – 7 carotid arteries, 8 , 9 and femoral arteries. 10 , 11 This report documents a case of active microcalcification in a lower extremity aneurysm and in below-the-knee arteries using 18 F-NaF PET/CT.…”
mentioning
confidence: 99%